Un zoologico en mi patio = Backyard zoo. - Rourke Publishing ([Vero Beach, Fla.] : Rourke Pub., 2010)
Colorful photographs and English and Spanish text teach children some of the everyday animals that can be found in an ordinary backyard. On board pages.
Colorful photographs and English and Spanish text teach children some of the everyday animals that can be found in an ordinary backyard.
Cover title.
Keywords: Garden animals -- Juvenile literature; Animals; Spanish language materials -- Bilingual -- Juvenile literature; Garden animals; Animals; Bilingual books